TEKANAN MENTAL GEN Z DI ERA KERJA DIGITAL: STUDI TENTANG KEPUASAN KERJA, BURNOUT, DAN KINERJA - Kesumayani, Heni (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the effect of mental workload and job satisfaction on Generation Z employee performance, with mental burnout as a mediating variable. A quantitative explanatory approach was applied by involving 200 Generation Z employees aged 18–28 years. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The findings reveal that mental workload positively affects mental burnout, while job satisfaction negatively affects mental burnout. Mental burnout has a negative effect on employee performance. In addition, mental workload negatively affects employee performance, whereas job satisfaction positively affects employee performance. The mediation results confirm that mental burnout partially mediates the relationship between mental workload and employee performance, as well as the relationship between job satisfaction and employee performance. These findings indicate that managing Generation Z employee performance should not rely solely on job satisfaction, compensation, or flexibility, but should also address mental pressure and psychological fatigue in digital work environments.